A quantitative analysis of trade policy responses to higher world agricultural commodity prices - Yu, T. Edward; Tokgoz, Simla; Wailes, Eric; Chavez, Eddie C. (International Food Policy Research Institute, 2017)
From 2007 through mid-2008, world prices of major agricultural commodities, such as cereals, oilseeds, and their by-products, experienced unprecedented surges since World War II (Baffes and Haniotis 2010).1 The world food price indexes produced by the Food and Agricultural Organization (FAO) of the United Nations increased by 56 percent between 2006 and 2008, while cereals and vegetable oils price indexes doubled during the same period (FAO 2010). Although price pressure for these commodities was temporarily relieved in late 2008 and 2009, the world price indexes for food, grains, and vegetable oils have rebounded in 2011 to their former high levels again (Figure 11.1). The sudden price spikes of agricultural and food commodities in 2007– 2008 quickly caught worldwide attention because cereal grains such as rice and wheat are staples in many developing economies, while corn is an important feedstock for the growing livestock sector in both developed and developing countries. For some food-deficit developing economies that rely heavily on imports for food consumption, drastic increases in the prices of these crops threatened the nutritional needs and social stability of these economies. Moreover, in major Asian rice-producing and rice-consuming countries, rice availability and affordability is a focus of national food security and policies (Wailes 2005).